2019
DOI: 10.1097/aud.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probe-Tone Frequency on Ipsilateral and Contralateral Electrical Stapedius Reflex Measurement in Children With Cochlear Implants

Abstract: Objectives: The upper loudness limit of electrical stimulation in cochlear implant patients is sometimes set using electrically elicited stapedius reflex thresholds (eSRTs), especially in children for whom reporting skills may be limited. In unilateral cochlear implant patients, eSRT levels are measured typically in the contralateral unimplanted ear because the ability to measure eSRTs in the implanted ear is likely to be limited due to the cochlear implant surgery and consequential changes in midd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The incidence of successful ESRT measurements in the present study was slightly higher than that of other studies. 3 12 16 The higher incidence of the measurable ESRTs in the present study could be because all the participants had normal tympanogram findings and individual electrode stimulation during ESRT measurements in the present study. The individual electrode stimulation enabled the presentation of higher CLs before reaching an uncomfortable level for the participants.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The incidence of successful ESRT measurements in the present study was slightly higher than that of other studies. 3 12 16 The higher incidence of the measurable ESRTs in the present study could be because all the participants had normal tympanogram findings and individual electrode stimulation during ESRT measurements in the present study. The individual electrode stimulation enabled the presentation of higher CLs before reaching an uncomfortable level for the participants.…”
Section: Discussionmentioning
confidence: 59%
“…The use of higher-frequency probe tones increases the success rate of ESRT measurements. In the study by Carranco Hernandez et al, 12 the success rates of ESRT measurements in children were of 58%, 68%, 68% for 226 Hz, 678 Hz, and 1,000 Hz respectively, when measured in contralateral non-implanted ears. In adult participants, Wolfe et al 11 reported that 13 out of 13 showed measurable ESRTs with 678 Hz or 1,000 Hz, and 12 out of 13 (92.3%), with 226 Hz.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations